Mechanical evidence that Australopithecus sediba was limited in its ability to eat hard foods - Justin A. Ledogar (Nature Portfolio, 2016)
Dietary adaptations of extinct early humans are often inferred from dental microwear data. Here, the authors employ mechanical analyses to show that Australopithecus sedibahad limited ability to consume hard foods.